# Evaluating the indefinite integral $\int\log\!\left(x+\sqrt{x^2-1}\right)\!dx$

I came across the following integral, and I don't know how to solve it. $$\int\log\left(x+\sqrt{x^2-1}\right)dx$$ I tried the "obvious" substitution of $x=\sec\theta$, which gives you: $$\int\tan\theta\sec\theta\log\left(\tan\theta+\sec\theta\right)d\theta$$ However, this doesn't simplify it much, in the sense that I have no idea how to solve this now! Take out the common factor of $\sec$ from the log, or perhaps do $u=\tan\theta+\sec\theta$, but both of these lead to dead ends (at least for me).

In case you are wondering, Wolfram|Alpha claims the answer is: $$x\log\left(x+\sqrt{x^2-1}\right)-\sqrt{x^2-1}+c$$

• Note that the integrand is just the inverse hyperbolic scoine function, $\text{arcosh } x$. en.wikipedia.org/wiki/… Jun 30, 2015 at 16:33
• (Rather, hyperbolic cosine function.) Jun 30, 2015 at 16:50
• (Also, presumably by "obvious substitution" you mean $x = \sec \theta$, so that the radical quantity simplifies to $\tan \theta$.) Jun 30, 2015 at 16:52
• If you follow Travis's suggestion of letting $x=\sec\theta$, you will get $\int\ln(\sec\theta+\tan\theta)\sec\theta\tan\theta d\theta$, and then you can use integration by parts (as in egreg's answer). Jun 30, 2015 at 17:46
• Sorry, got the substitution confused (although was correct on my paper!). I did mean $x=\sec\theta$, and I've corrected this now. Jul 1, 2015 at 9:58

Integrate by parts: $$x\log(x+\sqrt{x^2-1})-\int x\frac{1+\dfrac{x}{\sqrt{x^2-1}}}{x+\sqrt{x^2-1}}\,dx$$

Now, where did I see $\log(x+\sqrt{x^2-1})$ again? Set $x+\sqrt{x^2-1}=e^t$, so $$x^2-1=e^{2t}-2xe^t+x^2$$ or $$2xe^t=e^{2t}+1$$ and $$x=\cosh t$$ So a good substitution could be this one, wouldn't it? The integral becomes $$\int t\sinh t\,dt=t\cosh t-\int \cosh t\,dt=t\cosh t-\sinh t$$ and now it's just back substitution.

Computing directly shows that the integrand, $$\log\!\left(x + \sqrt{x^2 - 1}\right),$$ is the inverse of (the restriction to $[0, \infty)$ of) the hyperbolic cosine function $$\cosh u := \frac{e^u + e^{-u}}{2};$$ because of this, the integrand here is usually denoted $$\text{arcosh x}.$$

This suggests that we may proceed analogously to the usual derivation of the antiderivatives of inverse trigonometric functions: Substituting $x = \cosh u$ gives $$\int \text{arcosh } x \,dx = \int \text{arcosh} (\cosh u) \,d(\cosh u) = \int u \sinh u \,du.$$ Applying integration by parts with $v = u$, $dw = \sinh u \,du$ gives that this is $$u \cosh u - \int \cosh u\,du = u \cosh u - \sinh u + C,$$ and reverse-substituting to write this in terms of $x$ yields $$\text{arcosh } x \cosh (\text{arcosh } x) - \sinh(\text{arcosh } x) + C.$$

Substituting $u = \text{arcosh x}$ in the familiar identity $$\cosh^2 u = \sinh^2 u + 1,$$ simplifying, rearranging, and using that $\text{arcosh}$ is nonnegative (or, alternatively, appealing to the hyperbolic analogue of a reference triangle) gives the identity $$\sinh (\text{arcosh } x) = \sqrt{x^2 - 1}.$$ Substituing in the above expression gives the antiderivative, $$\color{#bf0000}{\int \text{arcosh } x \,dx = x \,\text{arcosh } x - \sqrt{x^2 - 1} + C},$$ which in particular agrees with the result given by WolframAlpha.

Recognize $$\log\left(x+\sqrt{x^2-1}\right)=\cosh^{-1}x$$ and then integrate by parts

$$\int\log\left(x+\sqrt{x^2-1}\right)dx=\int \cosh^{-1}x\>dx = x \cosh^{-1}x-\int \frac x{\sqrt{x^2-1}}dx$$ where the remaining integral is just $$\sqrt{x^2-1}$$.

$$\displaystyle \int ln(x+\sqrt{x^{2}-1})dx$$

$$\displaystyle {we've got }: \; \fbox{ ch^{2}(y)-sh^{2}(y)=1,ch(y)=\frac{e^{y}+e^{-y}}{2},sh(y)=\frac{e^{y}-e^{-y}}{2} }\\$$

$$\displaystyle x=ch(y)\Rightarrow dx=sh(y)dy$$

$$\displaystyle ln(x+\sqrt{x^{2}-1})=ln(ch(y)+sh(y))=y$$

$$\displaystyle \int ln(x+\sqrt{x^{2}-1})dx =\int y \ sh({y})dy=\int ych'(y)dy$$

$${we've got }: \;\fbox{ \displaystyle \int fg'=fg-\int f'g }$$

$$\displaystyle \int y \ sh({y})dy=y \ ch({y})-\int ch(y)dy=y \ ch({y})-\ sh({y})+c$$

$$\displaystyle \int ln(x+\sqrt{x^{2}-1})dx=xch^{-1}(x) -\sqrt{x^{2}-1}+c$$

$$\displaystyle =xln(x+\sqrt{x^{2}-1})-\sqrt{x^{2}-1}+c$$